Achieving sustained extrauterine life: Challenges of an artificial placenta in fetal pigs as a model of the preterm human fetus. Issue 5 (2nd March 2021) - Charest‐Pekeski, Alex J.; Sheta, Ayman; Taniguchi, Luiza; McVey, Mark J.; Floh, Alejandro; Sun, Liqun; Aujla, Tanroop; Cho, Steven K. S.; Ren, Jiaqi; Crawford‐Lean, Lynn; Foreman, Celeste; Lim, Jessie Mei; et al.
Abstract: Artificial placenta (AP) technology aims to maintain fetal circulation, while promoting the physiologic development of organs. Recent reports of experiments performed in sheep indicate the intrauterine environment can be recreated through the cannulation of umbilical vessels, replacement of the placenta with a low‐resistance membrane oxygenator, and incubation of the fetus in fluid. However, it remains to be seen whether animal fetuses similar in size to the extremely preterm human infant that have been proposed as a potential target for this technology can be supported in this way. Preterm Yucatan miniature piglets are similar in size to extremely preterm human infants and share similar umbilical cord anatomy, raising the possibility to serve as a good model to investigate the AP. To characterize fetal cardiovascular physiology, the carotid artery ( n  = 24) was cannulated in utero and umbilical vein (UV) and umbilical artery were sampled. Fetal UV flow was measured by MRI ( n  = 16). Piglets were delivered at 98 ± 4 days gestation (term = 115 days), cannulated, and supported on the AP ( n  = 12) for 684 ± 228 min (range 195–3077 min). UV flow was subphysiologic ( p  = .002), while heart rate was elevated on the AP compared with in utero controls ( p  = .0007). We observed an inverse relationship between heart rate and UV flow ( r 2  = .4527; p  < .001) with progressive right ventricular enlargement that was associated with reduced contractility and ultimately hydrops and circulatory collapse. We attribute this to excessive afterload imposed by supraphysiologic circuit resistance and augmented sympathetic activity. We conclude that short‐term support of the preterm piglet on the AP is feasible, although we have not been able to attain normal fetal physiology. In the future, we propose to investigate the feasibility of an AP circuit that incorporates a centrifugal pump in our miniature pig model. Abstract : The artificial placenta (AP) as an extrauterine environment to preserve fetal physiology and to promote fetal maturation forms a promising concept to reduce morbidity and mortality in the extremely premature. We have achieved successful transition of fetal minipigs on the AP but have encountered heart failure and fetal demise within several hours of support. Our experience highlights modes of failure and ways to improve AP technology to advance this approach to clinical application.